Fractionation of bio-oil using fractional distillation column for transportation liquid fuels - Hazellah, Muhammad Hadhari (2017)
The advancement of technology in transportation industries has been booming and the demands of fossil fuels is at its peak and need to be fulfilled. But conventional fuels such as petroleum and diesel will eventually be depleted in time and an immediate alternative solution is needed to meet the demands for fossil fuels. Introduction of bio-oil will serve as a new substitute for conventional fuels where it emits less pollution emission and act as renewable resources. Thus, the aim of this research is to produce bio-oil from Palm Kernel Shell (PKS) and Empty Fruit Bunch (EFB) by Fast Pyrolysis. The resulting crude bio-oil produced is cooled and collected before being sent for separation process (Fractionation Distillation). A total of 10 fractions of liquid bio-oil from the column is examined and analysed through physical and chemical analysis. Through physical analysis, the water content especially in the upper fraction of the column for EFB is higher than that in PKS bio-oil samples, and both PKS and EFB bio-oil pH values behaviour shows high degree of acidity level. In chemical analysis method, Fourier Transform Infrared Spectroscopy (FTIR) is used to detect functional groups in PKS and EFB bio-oil samples. Unlike EFB bio-oil analysis, PKS shows higher margin of deviation due to its temperature sensitive difference but still both produces rather similar trend of analysis. Lastly, Gas Chromatography-Mass Spectrometer (GC-MS) is used to identify numerous chemical composition of PKS and EFB bio-oil constituents.